As violações de direitos de crianças e adolescentes praticadas no âmbito familiar - Oliveira, Karina dos Santos (2017)
This dissertation aims to propose an examination ondomestic-based practices of children and adolescents rights violation, i.e. forms of violence in which a direct or indirect victim’s family member is involved. Thus, based on a theoretical reflection on what we can consider as being in the field of Sociology of the Family as well as the Sociology of Violence, the study sought firstly to understand how this institution, i.e. the family, which occupies a relevant symbolic position in society and on which an entire social imaginary based on stereotypes such as "protection", "care", "redoubt of moral and affective values", ends up as a space where aggression practices occur. For the research accomplishment, the occurrences notified to the Paracuru-Ce Tutelary Council were investigated. There was a link between qualitative and quantitative methodology. Among the techniques used are: participant observation, field diary, informal interviews and documentary analysis. The statistical analysis was performed through the Sphinx Software (a tool for quantitative and qualitative data analysis) in order to cross-check variables such as: type of violation, accused ones, whistleblower, complaint form, gender and age group of victims etc. A total of 3,741 occurrences were analyzed. In general, the results demonstrated that the most frequent violations were: negligence, physical violence, child laborexploitation and sexual violence. Among the main accused based on the family environment there are: parents (couple), mother, father, grandparents, stepfather, stepmother, uncles and brothers of the victim. Regarding whistle blowers, it was important to realize that even a family occupying the place as a "violator" of rights,it emerged as the main whistleblower in such cases. It is also highlighted that the most usual mean of performing the complaint is the face-to-face denunciation, i.e. the declarant is willing to go to the responsible organ in order to record the occurrence. Regarding the victims, the male audience was the most affected social group, although it has a quantitative representation very close to the female one. Regarding their age group, the index of occurrences with children stood out compared to the adolescents.